Empowering Supervisors Towards Responsible Research Conduct in Supervision via an Online Course: A Pilot Study - Mariëtte van den Hoven; Miriam van Loon (Center for Educational Policy Studies Journal)
Supervision and mentoring are highly relevant aspects of research integrity. Codes of Conduct, such as the ALLEA code of conduct, stipulate the relevance of training researchers how to conduct research well and about the role supervision plays in preventing unacceptable research practices. The Dutch Code of Conduct, for example, explicitly states that universities are responsible for facilitating training about research integrity. We developed a course for supervisors to address their responsibility and role in training early career researchers in research integrity. This contribution describes what evidence base was used to design this course and how the course is experienced by supervisors who participated in its piloting in early 2022. A total of 147 subscribed to the course in the testing phase, and seventeen participants obtained a certificate. The main lessons from the experiences with this course and the literature are 1) to tailor supervisor courses to the small amounts of time that supervisors can schedule to take these courses and to adjust the content and assignments to their needs, 2) to make online courses very attractive, but that need to be combined with 3) a face-to-face meeting to motivate them to finish the course in time and it might help to enable shared reflection by sharing personal experiences.